A Dual Component Catalytic System Composed of Non‐Noble Metal Oxides for Li–O2 Batteries with Enhanced Cyclability. (25th February 2016) - Zhao, Changtai; Yu, Chang; Yang, Juan; Liu, Shaohong; Zhang, Mengdi; Qiu, Jieshan
Abstract : One of the great challenges in the development of lithium–oxygen batteries (Li–O2 batteries) is to synthesize cost‐effective and efficient electrocatalysts to overcome several issues such as high charge overpotential and poor cycle life. Here, an efficient method is reported to fabricate a dual component electrocatalyst made of MnO2 nanoparticles supported on 1D Co3 O4 nanorods (MnO2 –Co3 O4 ), and its electrochemical behavior as a non‐noble metal cathode catalyst is demonstrated in Li–O2 batteries. It is found that the as‐made MnO2 –Co3 O4 catalyst exhibits an enhanced electrochemical performance, such as increased specific capacity (increase to 4023 mA h g −1 from 2993 mA h g −1 ), low charge overpotential (reduce 350 mV), high rate performance, and superior cyclability up to 150 cycles. The excellent electrochemical performance is attributed to the synergistic effects of the dual component catalytic system. Abstract : A dual component electrocatalyst made of MnO2 nanoparticles supported on 1D Co3 O4 nanorods (MnO2 –Co3 O4 ) is fabricated and its electrochemical behavior as a non‐noble metal cathode catalyst is demonstrated in Li–O2 batteries. Benefiting from the synergistic effects of the dual component catalytic system, low charge overpotential, high rate performance, and superior cyclability up to 150 cycles are achieved.